An analysis of Data mining TC-CMELPBC Technique in Weather Prediction (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The study was analysed “An analysis of Data mining TC-CMELPBC technique in weather prediction.” A random sample 1000-10,000 prediction reports on whether Atlantic hurricane Database has been served as subjects. The hypothesis was that whether the data mining TC-CMELPBC technique in prediction time using Atlantic hurricane Database has more efficient on weather forecasting. Results shows that experiment results of prediction time for existing the TC-CMELPBC technique. For the simulation setup, the number of data is considered in the range of 1000 to 10000. All three methods reduce the prediction time for detecting weather data. In big data, weather forecasting gives significant information about future weather. The changes in weather conditions are effectively identified by clustering and classification of similar data. Some of the existing research works developed for performing weather prediction while considering the large volume of data.